Factors Influencing Antibiotic Consumption in Adult Population of Kazakhstan - Nazym Iskakova; Zaituna Khismetova; Dana Suleymenova; Zhanat Kozhekenova; Zaituna Khamidullina; Umutzhan Samarova; Natalya Glushkova; Yuliya Semenova (MDPI AG, 2023)
Poor or suboptimal knowledge of appropriate antibiotic use is a cause for global concern and little is known about Central Asian countries. Therefore, this survey is aimed at evaluating awareness about antibiotic use and resistance among the adult population of Kazakhstan. A cross-sectional study of a random sample was conducted between October 2021 and February 2022 among 727 individuals without medical education and followed the methodology described in the WHO report "Antibiotic Resistance: Multi-country public awareness survey". Half of the respondents (50.4%) received antibiotic therapy within the last 12 months, 40.1% had no prescription for this and 40.4% received no advice from a medical professional. Nearly two-thirds of respondents (65.3%) never heard about antibiotic resistance and 57.2% believed that it is worth requesting the same antibiotic if it helped to treat a similar condition previously. In general, knowledge about antibiotic use proved to be low in 82.1% of respondents and 91.9% agreed with the statement that a common cold requires antibiotics. There is a need for awareness-raising campaigns to improve the knowledge about antibiotic use and resistance in the population of Kazakhstan.